Digitalization, Superstar Firms, and Labor Dynamics: evidence from France, Germany, Italy, Spain - Oleš, Tomáš (Ekonomický časopis/Journal of Economics, 2025)
This paper investigates the relationship between market concentration, firms’ size and labor productivity, wages, and labor share painted by the superstar firms hypothesis with an interaction of digital capital investments and intensities in four European economies making use of CompNet and EU-KLEMS data from 2005 to 2020. According to our findings, there is a negative and non-linear relationship between total factor productivity and labor share. At the industry level, there is a robust positive association between average industry concentration and labor productivity and wages. Negative correlation is found between industrial concentration and labor share, most notably in France. Within industries, there is again a consistent positive link between firms’ size and labor productivity, wages, and labor share decline. Additionally, increases in digital capital play an accelerating role in productivity and wages in the fourth and fifth quintiles of the firms’ size distribution. However, we found no significant accelerating or moderating impact on labor share declines across digitalization indicators and the firms’ size distribution.